Pandemic Crisis and Local Government Fiscal Health - Ненкова, Пресияна; Калчева, Десислава (Научни трудове, 2021)
The crisis brought on by the Covid-19 pandemic has strained the capacity of central governments and their healthcare systems but has also had an impact on the financial situation of local territorial units. Insofar as local authorities play an essential role in the enforcement of the lockdowns put in place to curb the pandemic, municipal spending has increased and the funds necessary to keep the measures in place have put an additional burden on municipal budgets, jeopardising essential public service delivery. This paper traces the changes in revenue and spending at local level in Bulgaria triggered by Covid-19 by looking at the level to which the crisis brought on by the pandemic has jeopardised the financial health of municipalities and contributed to an increase in the number of municipalities experiencing financial difficulties. In connection with this, the procedure for financial recovery of municipalities in Bulgaria and its effectiveness have been examined by looking at whether in the period 2016-2020 the number of municipalities experiencing financial difficulties has increased or decreased. The analysis covers the key factors that may lead to an increase in the number of municipalities with financial difficulties, including decreasing local tax collection rates, increasing municipal debt and arrears, etc. The capital activity of local authorities has also been explored. Measures for improving the local governments’ financial conditions and mitigating the negative effects of the crisis triggered by the pandemic have been proposed.
Keywords: Общински бюджети; Финансово възстановяване; България; Пандемична криза